2007
DOI: 10.1007/s10725-006-9142-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 5-sulfosalicylic acid on antioxidant activity in relation to vase life of Gladiolus cut flowers

Abstract: An experiment was conducted to study the effect of 5-sulfosalicylic acid (5-SSA) on the vase life of cut flowers of Gladiolus grandiflora variety 'Green Willow'. The vase solution having 5-SSA significantly increased cumulative uptake of vase solution, vase life, number of opened florets and decreased the number of unopened florets compared to the controls. Spikes kept in vase solution containing 5-SSA also exhibited lower respiration rates, lipid peroxidation and lipoxygenase (LOX) activity, and higher membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
67
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 46 publications
23
67
1
9
Order By: Relevance
“…Asil & Karimi (2010) applied Benzyl adenine (0, 25, 50 or 75 mg L -1 ) for improving quality and vase life of cut Eustoma flowers. It has been reported that all mentioned concentration of benzyladenine prolonged the vase life, although, spraying 25, 50 mgL -1 benzyladenine were more effective on extending vase life of cut Eustoma flowers, decreasing ethylelne production, reducing leaves chlorophyll and anthocyanin degradation beside that positive effects of salicylic acid on retarding flower senescence was represented (Ezhilmathi et al, 2007;Hatamzadeh et al, 2012). Ataii et al (2015) reported that spraying of salicylic acid delaying the postharvest senescence of Lisianthus cut flowers.…”
Section: Discussionmentioning
confidence: 99%
“…Asil & Karimi (2010) applied Benzyl adenine (0, 25, 50 or 75 mg L -1 ) for improving quality and vase life of cut Eustoma flowers. It has been reported that all mentioned concentration of benzyladenine prolonged the vase life, although, spraying 25, 50 mgL -1 benzyladenine were more effective on extending vase life of cut Eustoma flowers, decreasing ethylelne production, reducing leaves chlorophyll and anthocyanin degradation beside that positive effects of salicylic acid on retarding flower senescence was represented (Ezhilmathi et al, 2007;Hatamzadeh et al, 2012). Ataii et al (2015) reported that spraying of salicylic acid delaying the postharvest senescence of Lisianthus cut flowers.…”
Section: Discussionmentioning
confidence: 99%
“…The volume of the holding solution was 780 ml for each bottle. Control treatment contained 780 ml tap water + 4 % sucrose (Ezhilmathi et al 2007) while the other treatments contained 780 ml tap water +4% sucrose + specific chemical and its concentration.…”
Section: Methodsmentioning
confidence: 99%
“…These results may be probably due to that using 5-sulfosalicylic acid at a suitable concentration in vase solution led to decrease the respiration rate (Ezhilmathi et al 2007), delay senescence (Mackay et al 2000), activate photosynthesis rate (Senaratna et al 2000) and increase the vase solution uptake (Alaey et al 2011). All these attributes led to increase the cumulative synthesis materials in the cut gladiolus spikes, consequently the number of the fully opened florets per inflorescence could be increased.…”
Section: Floret Full Opening Period (Day)mentioning
confidence: 99%
“…The supernatant obtained after centrifugation at 4 •C was used to determine enzyme activity. CAT was measured by monitoring the decrease in hydrogen peroxide (H 2 O 2 ) at 240nm (11,12).…”
Section: Flowermentioning
confidence: 99%